Teacher's perceptions of policy and implementation of inclusive education at state junior high school in east Belitung regency - Miranda, Fryda; Dewanti, Septinda Rima (FOUNDASIA, 2024)
This research aims to describe teachers' perceptions of the policy and implementation of inclusive education at Junior High Schools in East Belitung Regency. Teacher perceptions are divided into three aspects, namely cognitive, affective and conative. This research is a descriptive quantitative approach with a survey research type. The subjects in this research were Junior High School teachers in East Belitung Regency with a sample size of 190 people. Data collection techniques use questionnaires. The data analysis technique used is quantitative descriptive analysis. This research found that 27,9% of teachers at Junior High School in East Belitung Regency have a positive perception toward inclusive education policy and 27,73% of teachers at Junior High School in East Belitung Regency have a positive perception toward implementation of inclusive education. Keywords: inclusive education policy, implementation of inclusive education, perception